The Influence of Role Awareness Training on Emotional Regulation and Psychological Well-being on Young Athletes - Rachman, Nabila; Nugraha, Difa Aditya; Sauda, Muhammad Aufa Al Farisi Ann Haba (Jurnal Psikologi Teori dan Terapan, 2024)
Abstract Background: Responding to the problem of double-career student-athletes during quarantine that resulted in an emotional regulation and psychological well-being crisis. Objective: To determine the effect of role awareness training on psychological well-being and emotional regulation in student-athletes. Method: Using quantitative experimental methods with a pre-test-posttest control group design. The subjects of this study were 24 athletes from the National Young Athlete Training Center UNESA. Sampling is done with a saturated sample, where all members of the population become samples. Data was obtained through pretests and posttests using psychological well-being tools containing 42 items. The data analysis technique used is an independent sample t test. Result: p value for emotional regulation is 0.027 and for psychological well-being is 0.047 (both p values are < 0.05). It shows training awareness of the role capable of guiding student-athletes in improving psychological well-being and emotional regulation. Conclusion: There is an influence of role awareness training on the emotional regulation and psychological well-being of student-athletes.   Abstrak Latar Belakang: Menanggapi permasalahan atlet pelajar yang berkarir ganda pada masa karantina yang mengakibatkan krisis regulasi emosi dan kesejahteraan psikologis. Tujuan: Untuk mengetahui pengaruh awareness training terhadap kesejahteraan psikologis dan regulasi emosi pada atlet pelajar. Metode: Penelitian ini menggunakan metode eksperimen kuantitatif dengan desain pretest dan posttest control group design. Subjek yang digunakan pada penelitian ini adalah para atlet Sentra Latihan Olahragawan Muda Potensial Nasional UNESA yang berjumlah 24 orang. Pengambilan sampel dilakukan dengan menggunakan jenis sampel jenuh, dimana seluruh anggota populasi menjadi sampel. Data diperoleh melalui pretest dan posttest dengan menggunakan alat bantu kesejahteraan psikologis yang berjumlah 42 item. Teknik analisis data yang digunakan adalah uji t sampel independen. Hasil: Nilai p untuk regulasi emosi sebesar 0,027 dan untuk kesejahteraan psikologis sebesar 0,047 (kedua nilai p < 0,05). Hal ini menunjukkan pelatihan kesadaran akan peran yang mampu membimbing pelajar-atlet dalam meningkatkan kesejahteraan psikologis dan regulasi emosional. Kesimpulan: Terdapat pengaruh awareness training terhadap regulasi emosi dan kesejahteraan psikologis atlet pelajar.